Discourses on social innovation and abandoned land reutilization pathways. A case study on riverside landscapes in a mountain area of Spain - Sanz-Hernández, Alexia; Jiménez-Caballero, Paula; Bacallao-Pino, Lázaro M.; Salvador Esteban, Raquel; Martín-Santafé, María (Frontiers in Forests and Global Change, 2022)
The article aims to analyze, based on a multiple case study, the discourses of the individuals that promote social innovation initiatives for the reuse of abandoned riverside landscapes, connecting social innovation theory with land reutilization and management through discourse analysis. Following a qualitative methodology, the text analyzes the characteristics of the promoting actors, the discourses storylines and the main actors’ discourses, describing some relevant aspects regarding social innovation, such as why, where and when it takes place; how it has been developed; who has promoted it; its main results, as well as the barriers faced for its development and future opportunities for the territory. Two main discursive tendencies are identified: a negationist trend and a possibilistic one, adopted by individuals who are not promoting initiatives of social innovation and by promoters of these kinds of experiences respectively. Possibilistic discourse underlines the coherent articulation between the economic-managerial dimension and the emotional-territorial one, and there is, in this case, a tendency to change in the visions of the territory, reconfiguring the social practices of the actors involved in these initiatives of social innovation. We conclude that discourses behind successful processes of social innovation are associated with certain positions on the interrelationships between individual-collective-institutionality-nature and that there is a complex articulation between discourses on social innovation and social practices developed by individuals as part of these initiatives, in such a reflexive way that discourses advance the desired changes, drawing and modifying the future vision of the subjects, and making the impossible possible.